2020
DOI: 10.1111/1759-7714.13395
|View full text |Cite
|
Sign up to set email alerts
|

Malignant solitary fibrous tumor occurring in the mediastinal pleura showing NAB2ex4‐STAT6ex2 fusion and negative STAT6 immunohistochemistry: A case report

Abstract: Solitary fibrous tumor (SFT) is a rare clinical tumor, defined as a mesenchymal tumor of fibroblastic origin. A classic SFT is benign in most cases, but its clinical behavior is unpredictable. Lately, molecular analyses has discovered that almost all SFTs harbor an NAB2-STAT6 fusion gene, which is considered specific to this tumor type. Recent studies have suggested that nuclear STAT6 immunoreactivity is a highly sensitive and specific marker of SFTs and can be helpful when diagnosis is inconclusive by convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Zhang et al. also reported a case with mediastinal malignant SFT carrying a NAB2-STAT6 fusion gene but negative STAT6 immunohistochemical staining ( 20 ). In the present case, the primary differentiated tumor was positive for CD34 and STAT6 but the primary dedifferentiated tumor and lung/liver metastases were completely negative ( Figures 3C, D, H, I ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. also reported a case with mediastinal malignant SFT carrying a NAB2-STAT6 fusion gene but negative STAT6 immunohistochemical staining ( 20 ). In the present case, the primary differentiated tumor was positive for CD34 and STAT6 but the primary dedifferentiated tumor and lung/liver metastases were completely negative ( Figures 3C, D, H, I ).…”
Section: Discussionmentioning
confidence: 99%
“…The most valuable positive markers of SFT immunohistochemistry were CD34, CD99, Bcl-2, and vimentin, cytokeratin (CK) was always negative. Recent studies have shown that nuclear STAT6 immunoreactivity is a highly sensitive and specific marker of SFT, and almost all SFT contain NP2-STAT6 fusion gene (39). The positive expression rate of STAT6 was even 100% in benign SFT but decreased in malignant SFT (40).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have claimed high specificity for STAT6 in the diagnosis of SFT 28,31,32. STAT6 IHC-negative SFTs have been rarely reported, and loss of STAT6 and CD34 has been associated with malignant biologic behavior in some cases 33. However, these cases demonstrated the NAB2::STAT6 translocation by molecular studies confirming the diagnosis; it is unclear whether the loss of these markers indicates a false-negative secondary to preanalytical variables or loss of expression through some other mechanism related to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%